Carbon quantum dot and carbon quantum dot derivative coated sodium ferric fluorophosphate composite material as well as preparation method and application thereof
By coating carbon quantum dots and their derivatives on the surface of sodium ferrophosphate material, the problems of low electronic conductivity and ion diffusion rate of sodium ferrophosphate material are solved, and the cyclic stability of the material and the improvement of the Coulomb efficiency are achieved.
Patent Information
- Application Number
- CN202411795251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
As the cathode material of sodium ion battery, sodium ferrous phosphate has low electronic conductivity and ion diffusion rate and low Coulomb efficiency, which limits its application.
By covering specific carbon quantum dots and their derivatives on the surface of sodium ferrophosphate material, a sodium ferrophosphate composite material coated with carbon quantum dots and their derivatives is formed to improve its cycle stability and Coulomb efficiency.
It effectively improves the cyclic stability and Coulombic efficiency of sodium fluorine phosphate material and improves its electrochemical performance.
Smart Images

Figure CN119725433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically, to a sodium iron fluorophosphate composite material coated with carbon quantum dots and derivatives thereof, and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries are considered an ideal large-scale energy storage technology due to their rich sodium resources and environmental friendliness. The large size of sodium ions makes it difficult to embed and diffuse in the positive electrode material. At the same time, the structure of the material changes more after embedding, so the specific capacity, kinetic performance and cycle performance of the electrode material are correspondingly deteriorated. Constructing high-capacity, long-cycle, high-stability sodium-ion batteries and developing simple and efficient preparation processes are what researchers need to pursue.
[0003] At present, the main materials widely used for the preparation of positive electrode materials are fluorophosphates, including vanadium-based alkali metal fluorophosphates, manganese-based alkali metal fluorophosphates and iron-based alkali metal fluorophosphates. These materials are expected to become the most promising positive electrode materials for sodium-ion batteries due to their advantages such as low price of synthetic materials, safe application, high working voltage and high theoretical specific capacity. Among them, sodium iron fluorophosphate, as an iron-based alkali metal fluorophosphate, has the advantages of low synthesis cost, simple chemical formula and high theoretical specific capacity. However, its electronic conductivity and ion diffusion rate are low, and its coulomb efficiency is low, which limits its application. Summary of the invention
[0004] Based on the above technical problems in the prior art, the present invention provides a sodium ferric fluorophosphate composite material coated with carbon quantum dots and their derivatives. The composite material includes a coating layer and a sodium ferric fluorophosphate material. By coating a specific carbon material layer on the surface of the sodium ferric fluorophosphate material, the cycle stability of the sodium ferric fluorophosphate material can be improved, and the first coulombic efficiency thereof can be improved.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A sodium ferric fluorophosphate composite material coated with carbon quantum dots and their derivatives, comprising a carbon coating layer and a sodium ferric fluorophosphate material, wherein the chemical formula of the sodium ferric fluorophosphate material is: Na 2 FePO 4 F; the carbon coating layer has a thickness of 5-10 nm, and the carbon content in the composite material is 5-10 wt %; the carbon coating layer is at least one of carbon quantum dots and their derivatives.
[0007] The present invention also provides a method for preparing the above-mentioned sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives, comprising the following steps:
[0008] S1. Weigh a sodium source, an iron source, a phosphorus source, a carbon source, a fluorine source and a complexing agent according to chemical measurements, add them to a solvent and mix them evenly to obtain a slurry;
[0009] S2, sand-grinding the slurry to a particle size D50≤30nm;
[0010] S3, spray drying the sand-milled slurry to obtain precursor particles;
[0011] S4, placing the precursor particles in a protective atmosphere, pre-sintering them, sintering them, and cooling them to obtain the sodium iron fluorophosphate composite material coated with the carbon quantum dots and their derivatives;
[0012] Wherein, the carbon source is at least one of carbon quantum dots and their derivatives.
[0013] In some embodiments, the carbon source is at least one of undoped carbon quantum dots, nitrogen-doped carbon quantum dots, sulfur-doped carbon quantum dots, phosphorus-doped carbon quantum dots, boron-doped carbon quantum dots, and graphene quantum dots.
[0014] In some embodiments, in step S4, the pre-sintering temperature is 300-400° C. and the pre-sintering time is 2-6 hours.
[0015] In some embodiments, the sintering temperature is 600-700° C. and the sintering time is 5-10 h.
[0016] In some embodiments, in step S1, the solid content of the slurry is 30-40%.
[0017] In some embodiments, in step S2, the grinding time is 6-8 hours.
[0018] In some embodiments, in step S3, the spray drying method is: the slurry enters the spray dryer through a peristaltic pump; wherein the feed rate is 3000-8000 ml / h, the inlet air temperature is 170-200°C, and the outlet air temperature is 85-110°C.
[0019] In some embodiments, the sodium source includes at least one of sodium carbonate, sodium pyrophosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium acetate, sodium acetate, and sodium formate.
[0020] In some embodiments, the iron source includes at least one of ferric chloride, ferric sulfate, ferric nitrate, and ferrous oxalate.
[0021] In some embodiments, the phosphorus source is at least one of sodium dihydrogen phosphate, phosphoric acid, and disodium hydrogen phosphate.
[0022] In some embodiments, the fluoride source is at least one of sodium fluoride, ammonium fluoride, hydrogen fluoride or potassium fluoride.
[0023] In some embodiments, the complexing agent includes at least one of citric acid, glucose, and cyclodextrin.
[0024] In some embodiments, the composite material has a particle size of 5-10 μm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention effectively improves the cycle stability and coulombic efficiency of the material by coating a specific carbon material layer on the surface of the sodium iron fluorophosphate material.
[0027] The preparation method of the present invention comprises the following steps: firstly mixing a sodium source, an iron source, a phosphorus source, a carbon source, a fluorine source and a complexing agent, and then sand-milling the mixture; then granulating the mixture by spray drying; and then pre-sintering the mixture in a protective atmosphere and then sintering the mixture to obtain a pure-phase sodium iron fluorophosphate composite material coated with carbon quantum dots; the addition of the complexing agent can not only effectively control the morphology of the composite material to obtain a spherical composite material, but also supplement the carbon source as a coating layer to further improve the structural stability of the composite material.
[0028] The sodium iron fluorophosphate coated with the carbon quantum dots and their derivatives obtained by the method of the present invention is applied to batteries and exhibits excellent cycle stability and coulombic efficiency, and has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the NFPF@CD composite material obtained in Example 1;
[0030] Figure 2 This is the XRD pattern of the NFPF@CD composite material obtained in Example 1. DETAILED DESCRIPTION
[0031] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] Example 1
[0034] A method for preparing a carbon quantum dot-coated sodium iron fluorophosphate composite material comprises the following steps:
[0035] S1. According to the chemical measurement, 5 mmol of sodium dihydrogen phosphate, 5 mmol of ferrous oxalate dihydrate, 5 mmol of sodium fluoride, 0.1 g of citric acid, and 0.15 g of carbon quantum dots were weighed as raw materials respectively;
[0036] S2. Add the raw materials into deionized water, stir in a sand mill, and grind to a particle size D50≤50nm; the stirring rate is 1000rpm, the sand mill power is set to 70kw, and the sand milling time is 7h to obtain a slurry;
[0037] S3, further diluting the slurry at a mass ratio of slurry: water = 3:4, and conveying the diluted slurry to a spray dryer through a peristaltic pump at a stirring speed of 500 rpm to prepare a sample, thereby obtaining precursor particles; wherein the feed rate is 3000 ml / h, the air inlet temperature is set to 170°C, and the air outlet temperature is 80°C;
[0038] S4. Place the precursor particles in an atmosphere furnace. Under the protection of a nitrogen atmosphere, first heat the temperature to 400°C at a rate of 3°C / min and keep it for 5 hours. Then heat the temperature to 650°C at the same rate and keep it for 10 hours. During the reaction, high-purity nitrogen (more than 99.9%) is continuously introduced. After the reaction, the sample is cooled with the furnace to obtain a carbon quantum dot-coated sodium iron fluorophosphate NFPF@CD composite material.
[0039] The obtained NFPF@CD composite material was characterized by SEM and XRD. Figure 1 and Figure 2 shown.
[0040] like Figure 1 The NFPF@CD composite material prepared in this embodiment is spherical and has a uniform particle size of 5-10 μm.
[0041] like Figure 2 As shown, the NFPF@CD composite material prepared in this embodiment has good crystallinity, and the internal particles are Na 2 FePO 4 F pure phase.
[0042] Example 2
[0043] A method for preparing a nitrogen-doped carbon quantum dot-coated sodium iron fluorophosphate composite material comprises the following steps:
[0044] S1. According to the stoichiometric amount, 5 mmol of sodium dihydrogen phosphate, 5 mmol of ferrous oxalate dihydrate, 5 mmol of sodium fluoride, 0.1 g of citric acid, and 0.15 g of nitrogen-doped carbon quantum dots were weighed as raw materials;
[0045] S2. Add the raw materials into deionized water, stir in a sand mill, and grind to a particle size D50≤50nm; the stirring rate is 1000rpm, the sand mill power is set to 70kw, and the sand milling time is 7h to obtain a slurry;
[0046] S3, further diluting the slurry at a mass ratio of slurry: water = 3:4, and conveying the diluted slurry to a spray dryer through a peristaltic pump at a stirring speed of 500 rpm to prepare a sample, thereby obtaining precursor particles; wherein the feed rate is 3000 ml / h, the air inlet temperature is set to 170°C, and the air outlet temperature is 80°C;
[0047] S4. Place the precursor particles in an atmosphere furnace, and under the protection of a nitrogen atmosphere, first heat the temperature to 400°C at a rate of 3°C / min and keep it for 5 hours, then heat the temperature to 650°C at the same heating rate and keep it for 10 hours. During the reaction, high-purity nitrogen (more than 99.9%) is continuously introduced. After the reaction is completed, the sample is cooled with the furnace to obtain a nitrogen-doped carbon quantum dot-coated sodium iron fluorophosphate NFPF@NCD composite material.
[0048] Example 3
[0049] A method for preparing a fluorine-doped carbon quantum dot-coated sodium iron fluorophosphate composite material comprises the following steps:
[0050] S1. According to the chemical measurement, 5 mmol of sodium dihydrogen phosphate, 5 mmol of ferrous oxalate dihydrate, 5 mmol of sodium fluoride, 0.1 g of citric acid, and 0.15 g of fluorine-doped carbon quantum dots were weighed as raw materials respectively;
[0051] S2. Add the raw materials into deionized water, stir in a sand mill, and grind to a particle size D50≤50nm; the stirring rate is 1000rpm, the sand mill power is set to 70kw, and the sand milling time is 7h to obtain a slurry;
[0052] S3, further diluting the slurry at a mass ratio of slurry: water = 3:4, and conveying the diluted slurry to a spray dryer through a peristaltic pump at a stirring speed of 500 rpm to prepare a sample, thereby obtaining precursor particles; wherein the feed rate is 3000 ml / h, the air inlet temperature is set to 170°C, and the air outlet temperature is 80°C;
[0053] S4. Place the precursor particles in an atmosphere furnace, and under the protection of a nitrogen atmosphere, first heat the temperature to 400°C at a rate of 3°C / min and keep it for 5 hours, then heat the temperature to 650°C at the same heating rate and keep it for 10 hours. During the reaction, high-purity nitrogen (more than 99.9%) is continuously introduced. After the reaction is completed, the sample is cooled with the furnace to obtain a carbon quantum dot-coated sodium iron fluorophosphate NFPF@FCD composite material.
[0054] Comparative Example 1
[0055] A method for preparing a carbon-coated sodium iron fluorophosphate composite material comprises the following steps:
[0056] S1. According to the chemical measurement, 5 mmol of sodium dihydrogen phosphate, 5 mmol of ferrous oxalate dihydrate, 5 mmol of sodium fluoride, and 0.25 g of citric acid were weighed as raw materials;
[0057] S2. Add the raw materials into deionized water, stir in a sand mill, and grind to a particle size D50≤50nm; the stirring rate is 1000rpm, the sand mill power is set to 70kw, and the sand milling time is 7h to obtain a slurry;
[0058] S3, further diluting the slurry at a mass ratio of slurry: water = 3:4, and conveying the diluted slurry to a spray dryer through a peristaltic pump at a stirring speed of 500 rpm to prepare a sample, thereby obtaining precursor particles; wherein the feed rate is 3000 ml / h, the air inlet temperature is set to 170°C, and the air outlet temperature is 80°C;
[0059] S4. Place the precursor particles in an atmosphere furnace, and under the protection of a nitrogen atmosphere, first heat the temperature to 400°C at a rate of 3°C / min and keep it for 5 hours, then heat the temperature to 650°C at the same heating rate and keep it for 10 hours. During the reaction, high-purity nitrogen (more than 99.9%) is continuously introduced. After the reaction is completed, the sample is cooled with the furnace to obtain a carbon-coated sodium iron fluorophosphate NFPF@C composite material.
[0060] Comparative Example 2
[0061] A method for preparing a carbon quantum dot-coated sodium iron fluorophosphate composite material comprises the following steps:
[0062] S1. According to the chemical measurement, 5 mmol of sodium dihydrogen phosphate, 5 mmol of ferrous oxalate dihydrate, 5 mmol of sodium fluoride, and 0.25 g of carbon quantum dots were weighed as raw materials respectively;
[0063] S2. Add the raw materials into deionized water, stir in a sand mill, and grind to a particle size D50≤50nm; the stirring rate is 1000rpm, the sand mill power is set to 70kw, and the sand milling time is 7h to obtain a slurry;
[0064] S3, further diluting the slurry at a mass ratio of slurry: water = 3:4, and conveying the diluted slurry to a spray dryer through a peristaltic pump at a stirring speed of 500 rpm to prepare a sample, thereby obtaining precursor particles; wherein the feed rate is 3000 ml / h, the air inlet temperature is set to 170°C, and the air outlet temperature is 80°C;
[0065] S4. Place the precursor particles in an atmosphere furnace. Under the protection of a nitrogen atmosphere, first heat the temperature to 400°C at a rate of 3°C / min and keep it for 5 hours. Then heat the temperature to 650°C at the same rate and keep it for 10 hours. During the reaction, high-purity nitrogen (more than 99.9%) is continuously introduced. After the reaction, the sample is cooled with the furnace to obtain a carbon quantum dot-coated sodium iron fluorophosphate NFPF@CD composite material.
[0066] The composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as positive electrode active materials, and were mixed in a mass ratio of positive electrode active material, conductive agent carbon black: binder PVDF of 8:1:1. After sufficient grinding, an appropriate amount of NMP was added to obtain a uniform slurry. The slurry was coated on an aluminum foil current collector, placed in a vacuum drying oven, dried at 70°C, and then taken out and cut into discs. A metallic sodium sheet was used as a counter electrode; 1M NaClO4 / EC:DMC:EMC (1:1:1) was used as an electrolyte, and button cells were assembled and then electrochemical performance tests were performed.
[0067] The test results are shown in Table 1
[0068] Table 1 Electrochemical performance test results of the composite materials of Examples 1-3 and Comparative Examples 1-2
[0069]
[0070] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0071] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite material of sodium iron fluorophosphate coated with carbon quantum dots and their derivatives, characterized in that: It comprises a carbon coating layer and a sodium iron fluoride phosphate material, wherein the chemical formula of the sodium iron fluoride phosphate material is: Na2FePO4F; the thickness of the carbon coating layer is 5-10nm, and the carbon content in the composite material is 5-10wt%; the carbon coating layer is at least one of carbon quantum dots and their derivatives.
2. The method for preparing the sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives according to claim 1, characterized in that: The following steps are involved: S1. Weigh a sodium source, an iron source, a phosphorus source, a carbon source, a fluorine source and a complexing agent according to chemical measurements, add them to a solvent and mix them evenly to obtain a slurry; S2, sand-grinding the slurry to a particle size D50≤30nm; S3, spray drying the sand-milled slurry to obtain precursor particles; S4, placing the precursor particles in a protective atmosphere, pre-sintering them, sintering them, and cooling them to obtain the sodium iron fluorophosphate composite material coated with the carbon quantum dots and their derivatives; Wherein, the carbon source is at least one of carbon quantum dots and their derivatives.
3. The method for preparing the sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives according to claim 2, characterized in that: The carbon source is at least one of undoped carbon quantum dots, nitrogen-doped carbon quantum dots, sulfur-doped carbon quantum dots, phosphorus-doped carbon quantum dots, boron-doped carbon quantum dots, and graphene quantum dots.
4. The method for preparing the sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives according to claim 2, characterized in that: In step S4, the pre-sintering temperature is 300-400°C; and the sintering temperature is 600-700°C.
5. The method for preparing the sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives according to claim 2, characterized in that: In step S1, the solid content of the slurry is 30-40%.
6. The method for preparing the sodium iron fluorophosphate composite material coated with carbon quantum dots and their derivatives according to claim 2, characterized in that: In step S3, the spray drying method is: the slurry enters the spray dryer through a peristaltic pump; wherein the feed rate is 3000-8000 ml / h, the inlet air temperature is 170-200°C, and the outlet air temperature is 85-110°C.
7. An electrode active material, characterized in that It comprises the sodium iron fluorophosphate composite material coated with the carbon quantum dots and their derivatives as claimed in claim 1.
8. A positive electrode material, characterized in that Comprising the electrode active material according to claim 7.
9. A positive electrode, characterized in that Comprising the positive electrode material as claimed in claim 8.
10. An electrochemical energy storage device, characterized in that: Comprising the positive electrode as claimed in claim 9.
Citation Information
Cited By
Sodium ferric fluorophosphate positive electrode material with wide interlayer spacing and two-dimensional lamellar structure and preparation method of sodium ferric fluorophosphate positive electrode material
CN121035204A